CFD Investigation on the Aerodynamic Interferences between Medium-solidity Darrieus Vertical Axis Wind Turbines. (December 2015) - Giorgetti, Simone; Pellegrini, Giulio; Zanforlin, Stefania
Abstract: The present study contributes to understand physical mechanisms involved in an achievable power enhancement by setting vertical axis wind turbines in close proximity. The turbines are straight-bladed Darrieus micro-turbines characterized by medium-high solidity and therefore low tip-speed ratio. Preliminary CFD simulations of the isolated turbine explain the reasons why it has a low power output, namely which are laminar flow and laminar separation bubbles on the blades. This fact is expected also considering the low Reynolds number. Subsequently a campaign of CFD simulations has been performed to analyse the aerodynamic interferences in two-rotor configurations. The behaviour of counter-rotating and co-rotating arrangements is analysed at different distances between rotor axes. The simulations show an increasing of power production of about 10% compared to results for the isolated turbine, independently of the sense of rotation. In order to verify wheter vortex shedding suppression might be the cause of the enhanced performance interactions has been simulated between two closely spaced Magnus spinning cylinders with the same tip-speed ratio of the turbines. These last results don't show reasonable analogies with VAWT wake structures and interactions. Our main conclusion is that accelerated free-stream flow between the turbines is the principle cause of the power extraction enhancement by means of contraction and re-energisation of the turbine wakes. CFD predictions of a four-rotor configuration confirm our hypothesis, nevertheless the wind direction strongly affects the overall efficacy.